Antibody response and safety of inactivated SARS-CoV-2 vaccines in chronic hepatitis B patients with and without cirrhosis - Cao, Huanhuan; Huang, Yufei; Zhong, Chunxiu; Liao, Xingmei; Tan, Wenjuan; Zhao, Siru; Guo, Liangxu; Fan, Rong (Frontiers in Immunology, 2023)
Background: The immune response and safety of inactivated SARS-CoV-2 vaccines among chronic hepatitis B (CHB) patients, especially those with cirrhosis, are uncertain. Therefore, we conducted this study to evaluate the efficacy and safety of inactivated SARS-CoV-2 vaccines among CHB patients with or without cirrhosis. Patients and methods: A total of 643 CHB patients who received two doses of the inactivated SARS-CoV-2 vaccine (BBIBP-CorV and CoronaVac) were enrolled. Serum samples were collected and tested for SARS-CoV-2-RBD IgG at enrollment. Adverse events (AEs) within 7 days after the second dose were obtained by questionnaire. Results: A total of 416 noncirrhotic and 227 cirrhotic patients were included in the analysis. The cirrhotic patients had lower antibody titers than the noncirrhotic patients after adjusting for age, sex and interval time (2.45 vs. 2.60 ng/ml, p =0.034). Furthermore, the study revealed that cirrhotic patients demonstrated a slower rate of seropositivity increase, with the highest rate being recorded at week 4 and reaching 94.7%, while among the noncirrhotic patients, the seropositivity rate peak was observed at week 2 and reached 96.0%. Additionally, cirrhotic patients displayed a more rapid decline in the seropositivity rate, dropping to 54.5% after ≥16 weeks, while noncirrhotic patients exhibited a decrease to 67.2% after the same time period. The overall incidence of AEs was low (18.4%), and all AEs were mild and self-limiting. In addition, 16.0% of participants had mild liver function abnormalities, and half of them returned to normality within the next six months without additional therapy. The participants who experienced liver function abnormalities showed a higher seropositivity rate and antibody titer than those who did not (91.6% vs. 79.5%, p =0.005; 2.73 vs. 2.41 ng/ml, p <0.001). Conclusion: Cirrhotic CHB patients had lower antibody titers to inactivated SARS-CoV-2 vaccines than noncirrhotic patients. Vaccines were generally well tolerated in both noncirrhotic and cirrhotic CHB patients. Patients with abnormal liver function may have a better antibody response than those without.